2004
DOI: 10.1590/s0085-56262004000100015
|View full text |Cite
|
Sign up to set email alerts
|

Levantamento das espécies de Simulium (Diptera, Simuliidae), Riacho dos Padres, município de Almirante Tamandaré, Paraná, Brasil

Abstract: ABSTRACT. Survey of the Simulium species (Diptera, Simuliidae), Riacho dos Padres, Almirante Tamandaré municipality, Paraná, Brazil. From January to August 2002, collections of simuliid larvae, both in natural and anthropic substrates, were carried out biweekly in Riacho dos Padres. This study provides a local inventory of species and their relative frequencies. The area is a private property located in the Curitiba metropolitan area, and it is dedicated mainly to farming fish, rabbits, sheep, cattle, poultry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
2
2
0
2
Order By: Relevance
“…The simuliid richness observed in the Comandaí river subbasin represents 39.28% of all the reported species for the state of Rio Grande do Sul, and 6.79% of the total sampled species current reported for Brazil (Adler 2021). From the eleven sampled species in this study, S. pertinax (77.55%) showed the highest abundance and frequency of occurrence, a similar result was observed in other studies carried out in several other watersheds from Rio Grande do Sul (strieder 2004;strieder et al 2006;sAntos et al 2007;BertAzo et al 2013;CouCeiro et al 2014;menzel et al 2019), as well as in other Brazilian states (CunHA 2004;lozovei et al 2004;Coppo & lopes 2010;ArAndA 2017;Figueiró et al 2020). This species adapts easily to different micro-habitats, and currently occurs in 17 of the 27 Brazilian states, in addition to other South American countries such as Argentina, Bolivia and Paraguay (Adler 2020).…”
Section: Discussionsupporting
confidence: 89%
“…The simuliid richness observed in the Comandaí river subbasin represents 39.28% of all the reported species for the state of Rio Grande do Sul, and 6.79% of the total sampled species current reported for Brazil (Adler 2021). From the eleven sampled species in this study, S. pertinax (77.55%) showed the highest abundance and frequency of occurrence, a similar result was observed in other studies carried out in several other watersheds from Rio Grande do Sul (strieder 2004;strieder et al 2006;sAntos et al 2007;BertAzo et al 2013;CouCeiro et al 2014;menzel et al 2019), as well as in other Brazilian states (CunHA 2004;lozovei et al 2004;Coppo & lopes 2010;ArAndA 2017;Figueiró et al 2020). This species adapts easily to different micro-habitats, and currently occurs in 17 of the 27 Brazilian states, in addition to other South American countries such as Argentina, Bolivia and Paraguay (Adler 2020).…”
Section: Discussionsupporting
confidence: 89%
“…Recent literature indicated seven species breeding in the same location of the present research (Lozovei et al, 2004). In descending order of prevalence, the species were S. inaequale (34.91%), S. pertinax (19.74%), S. orbitale (18.75%), S. perflavum (14.85%), S. subnigrum (9.84%), S. distinctum (1.68%) and S. incrustatum (0.23%).…”
Section: Resultssupporting
confidence: 58%
“…Moreover, several species can share the same breeding site, with each one presenting a different life cycle duration and oviposition preference to a specific substrate. Recent work carried out in the same location of this study revealed the presence of seven species breeding in the "Riacho dos Padres" river closed to Almirante Tamandaré town (Lozovei et al, 2004 Lutz, 1910. The aim of the present work was to better understand egg fertility and aspects related to the life cycle of immature stages of Simulium spp from egg to adult.…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…Simulídeos são insetos holometábo-los, e suas larvas são filtradores não seletivos, ingerindo partículas inferiores a 100 μm, característica que as torna o principal alvo para atividades de controle, uma vez que as pupas não se alimentam e os alados apresentam maior dispersão, características que dificultam a formulação de estraté-gias eficazes de controle com inseticidas (Cunha, 2004). Desta forma, várias investigações sobre aspectos bioecológicos da fase larval deste díptero têm sido realizadas (Zhang, 2000;Lozovei et al, 2004;Silva et al, 2009) …”
Section: Introductionunclassified